The influence of anthropometric indicators on the availability of vitamin D in residents of Southern Ukraine - Shanyhin, Anton; Babienko, Volodymyr; Rozhnova, Anastasiya; Strakhov, Yevhen (Journal of Education, Health and Sport, 2023)
The social role of the problem of obesity is determined by the threat of disability and a decrease in overall life expectancy due to the frequent development of serious concomitant diseases. Despite a significant number of studies on the effect of excess body weight on the level of 25(OH)D, there are still ongoing discussions about the role of vitamin D in the pathogenesis of obesity. The main described pathogenetic mechanism by which obesity negatively affects 25(OH)D levels is the redistribution of fat-soluble vitamin D in large amounts of adipose tissue. This leads to a decrease in the concentration of 25(OH)D in the blood serum. Goal. To determine the dependence of the level of 25(OH)D in blood serum on anthropometric indicators in residents of the southern regions of Ukraine. Materials and methods. During the study, 928 residents (women – 507; men – 421) of southern Ukraine aged 19 to 82 were examined. The results. The level of 25(OH)D in blood serum among the study participants ranged from 4.31 - 89.19 ng/ml. The prevalence of deficiency, insufficiency and sufficient level of vitamin D in the study group was 33.6%, 33% and 33.4%, respectively. The body mass index in the study group ranged from 16.1 kg/m2 to 41.3 kg/m2, while the average BMI in men was 25.2±4.0 kg/m2, and in women it was 25.6±4.5 kg/m2. In addition, an anthropometric analysis was conducted, namely, a waist-to-hip ratio assessment was conducted in order to determine the influence of these indicators on the level of 25(ОН)D in blood serum. Conclusions. A higher negative correlation was established between the level of 25(OH)D and BMI than the waist-to-hip ratio index. The hypothesis of the connection of vitamin D with the specified anthropometric indicators was confirmed, in particular, when comparing groups by BMI. It is worth noting that among people of both sexes, regardless of age, with an increase in BMI and waist circumference, a decrease in the level of 25(OH)D in blood serum is observed.